A new restorative method for the closure of single-tooth gaps: technique description and case series - Staehle, Hans Jörg (The journal of adhesive dentistry, 2019)
PURPOSE: To present a new method for the closure of single-tooth gaps using metal-, ceramic-, and glass-fiber-free direct composite cantilever restorations. MATERIALS AND METHODS: The new technique is described step by step in a case report, showing the creation and adhesive bonding of a single-retainer composite pontic. Furthermore, six cases are reported with radiological and clinical follow-up assessments over a period of one to three years after gap closure. RESULTS: Excellent outcomes were observed clinically and radiologically. No failures due to material properties (such as composite fractures, chipping) or esthetic limitations through discoloration were observed. Due to good oral hygiene, no periodontal complications were found during the observation period. CONCLUSIONS: This new minimally invasive procedure expands the therapeutic spectrum for the management of single-tooth gaps. It does not require laboratory-fabricated restorations and can be considered when conventional treatments, such as fixed dental prostheses or implants, are not options for medical reasons or due to special patient preferences.
Gesehen am 25.02.2020